Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.4 - Adding and Subtracting Rational Expressions with Different Denominators - Exercise Set - Page 517: 63



Work Step by Step

$\frac{8x+7}{3x+5}$-$\frac{2x-3}{3x+5}$= $\frac{8x+7-(2x-3)}{3x+5}$= $\frac{8x+7-2x+3}{3x+5}$= $\frac{6x+10}{3x+5}$=$\frac{2(3x+5)}{3x+5}$ = 2
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.